Motorcycle Child Seat for Child with Special needs: Its Design Process and Problem-based Learning - Ihza Lisiano Al Qushai; Arnaz Sholeh; Wahyu Nur Budiarta; Farid Triawan (Universitas Pendidikan Indonesia (UPI), 2021)
Most of child safety seats for motorcycle available in Indonesian market do not provide enough safety for the children passenger, especially for special needs child. This makes a special needs child cannot ride a motorcycle and prefer to use an automobile for their transportation means. However, it becomes a problem for a low-income family that can only afford a motorcycle. To address this problem, the present work aims to i) design a portable child safety seat for those with special needs that can be placed at the back side of the motorcycle, ii) provide safety feeling to the child by making a capsule-like shape for overall protection, iii) demonstrate an education case-study for mechanical design course. Discussion on how to determine the specification based on problem definition as well as the explanation on the design process of seat’s frame and body are provided. This work can be also used a reference for problem-based learning in mechanical engineering design course.